Numerical modeling of normal fault-pipeline interaction and comparison with centrifuge tests. Issue 105 (February 2018) - Ni, Pengpeng; Moore, Ian D.; Take, W. Andy
Abstract: Pipelines extend thousands of kilometers across wide geographic areas to provide products for modern life. It is inevitable therefore that pipelines must pass through active faulting zones. The safety of pipe networks should be maintained by employing an appropriate design method. Beam-on-spring analysis is the normal design approach, but it is difficult to choose the spring stiffness for pipelines crossing a dip-slip (normal/reverse) fault, since the native soils beneath the pipe trench may provide extra restraints on relative pipe-soil movement. Alternatively, three-dimensional finite element analysis has the potential to provide useful design calculations which account for (a) axial and flexural stiffness of the pipe, (b) geometry and kinematics of the problem (including the actual trench size and correct ground motion), (c) stiffness of the pipe relative to the soil stiffness assembled from the different components of the surrounding soil (the undisturbed native soil material, the bedding soil, the sidefill and the backfill), and (d) nonlinear effects like formation of gaps and shear failure of the soil. Using geotechnical centrifuge test measurements, three-dimensional finite element models are developed to capture the behaviours observed for buried pipelines of various materials subjected to differential ground movements associated with normal faulting. Material nonlinearity, geometric nonlinearity, and the contact, detachment and slippage behaviour on the soil-pipe interface are explicitly modeled. Using hexahedron continuum elements, satisfactory reproductions of the centrifuge experiments are achieved for flexural responses of the test pipes. The finite element analysis is then used to investigate the impact of trench burial conditions. Highlights: Three dimensional finite element modeling is used to study pipelines crossing normal ground faults. Effect of pipeline stiffness on maximum curvature is examined. Analyses are compared to tests conducted on four different pipe models in a geotechnical centrifuge. Finite element analysis with standard constitutive models provides reliable calculations provided mesh is adequately refined. The use of the analysis is then illustrated by examining the impact of trench burial.